Beta, gamma-Bis-substituted PNA with configurational and conformational switch: preferred binding to cDNA/RNA and cell-uptake studies - Bose, Tanaya; Banerjee, Anjan; Nahar, Smita; Maiti, Souvik; Kumar, Vaijayanti A. (Chemical Communications, 2015)
(S,S)- and (R,R)-beta,gamma-Bis-substituted PNAs were synthesized from the C-2 symmetric vicinal diamine system embedded in 1,4 dihydroxybutane and 1,4-dimethoxybutane scaffolds. (R,R)-beta,gamma-Bis-methoxymethyl-PNA derived from D-tartaric acid was found to be in the right configuration and conformation to be an excellent mimic of PNA, endowed with superior ability to enter into cells.